A novel wake model for wind farm design on complex terrains. Issue 174 (March 2018) - Kuo, Jim; Rehman, Danyal; Romero, David A.; Amon, Cristina H.
Abstract: A numerical wake model that is capable of simulating wind turbine wake effects over complex terrains is proposed in this work. Currently, full computational fluid dynamics (CFD) simulations are required to simulate wake effects over complex terrains. Due to their high computational cost, it is difficult to apply expensive CFD simulations in the wind farm design process as optimization algorithms often require large number of solution evaluations. The proposed wake model solves a simplified variation of the Navier-Stokes equations, in which simplifications and assumptions have been implemented in order to reduce computational cost while maintaining accuracy. This model was validated by comparing with full CFD simulations with reasonable accuracy. In general, the model produces accurate results while keeping the computational cost two orders of magnitude lower than that of full CFD simulations. The low computation time highlights the model's potential to be used for optimizing wind farm layouts on complex terrains. Highlights: A fast and accurate wake model for simulating wakes on complex terrain is proposed. The accuracy of the model has been validated with full CFD simulations. The model solves at least 2 orders magnitude faster than full CFD simulations.